Herbal Phytochemicals as Immunomodulators - R. Cundell, Diana (Current Immunology Reviews (Discontinued), 2014)
Herbal medicines are a mainstay in most Asian countries and have been used successfully for thousands of years to modulate immune system function. At least thirty herbs and plants fall into this category, with many having been developed for usage as “classic” pharmaceutical agents. This paper will review the discovery (if known), usage and scientific evidence for the biological and chemical activity behind the botanical products commonly used to boost or inhibit immune system function. Issues with production purity, shelf life and effectiveness of each herbal and plant moiety will also be discussed.
Keywords: phytochemical